Diagnostic Expectations and Stock Returns - BORDALO, PEDRO; GENNAIOLI, NICOLA; PORTA, RAFAEL LA; SHLEIFER, ANDREI (Journal of Finance, 2019)
ABSTRACT We revisit La Porta's finding that returns on stocks with the most optimistic analyst long‐term earnings growth forecasts are lower than those on stocks with the most pessimistic forecasts. We document the joint dynamics of fundamentals, expectations, and returns of these portfolios, and explain the facts using a model of belief formation based on the representativeness heuristic. Analysts forecast fundamentals from observed earnings growth, but overreact to news by exaggerating the probability of states that have become more likely. We find support for the model's predictions. A quantitative estimation of the model accounts for the key patterns in the data.